Carpal Tunnel Syndrome in Pregnancy (Medical Forum Monthly, 2024)
Objective: To determine the frequency, severity and prognosis of carpal tunnel syndrome (CTS) in pregnancy.Study Design: Descriptive Cross -sectional studyPlace and duration of Study: This study was conducted in Gynae “B” Unit of Khyber Teaching Hospital, Peshawar from Apr 2012 to Mar 2013Materials and Methods: During the study period, pregnant women presenting to Antenatal Outpatient Department of Gynae B unit were randomly assessed for carpal tunnel syndrome. If present, severity of CTS and its relation to age, trimester of pregnancy, weight gain during pregnancy, parity and any underlying medical problem was made. Treatment was advised and response to treatment was assessed. Patients were followed up for outcome.Results: Of 1000 Pregnant women assessed, 22.3% had symptoms and signs suggestive of CTS. Bilateral (68%) paresthesia (82%) and pain (60%) in third trimester of pregnancy were the most frequent presenting symptoms. It was more common in >30 years old mutigravidae and with a weight gain in pregnancy of more than 15kg. Majority (95%) of patients responded to splinting of wrist at night.Conclusion: Carpal tunnel syndrome is common during third trimester of pregnancy especially in mutigravidae who gain more weight during pregnancy and are above 30 years of age. CTS severe enough to warrant surgical treatment occurs infrequently in pregnancy and generally responds to conservative treatment.